Feed your microbiome and improve sleep, stress resilience, and cognition - Maciej Chichlowski; Jack Cotter; Neil Fawkes; Neeraj Pandey (Open Exploration Publishing Inc., 2022)
The brain and gut are connected both physically and biochemically. The gut-brain axis includes the central nervous system, neuroendocrine and neuroimmune systems, the enteric nervous system and vagus nerve, and the gut microbiome. It can influence brain function and even behavior, suggesting that dietary interventions may help enhance and protect mental health and cognitive performance. This review focuses on the role of the microbiome and its metabolites in sleep regulation, neurodegenerative disorders, mechanisms of stress, and mood. It also provides examples of nutritional interventions which can restore healthy gut microbiota and aid with risk reduction and management of many disorders related to mental and cognitive health. Evidence suggests a shift in the gut microbiota towards a balanced composition could be a target to maintain brain health, reduce stress and improve quality of life.